2018
DOI: 10.1088/1367-2630/aae8a8
|View full text |Cite
|
Sign up to set email alerts
|

Topological defects in weak perpendicular magnetic anisotropy NdCo honeycomb lattices

Abstract: Domain configuration has been studied by magnetic force microscopy and micromagnetic simulations in NdCo honeycomb lattices in comparison with similar patterned structures made of polycrystalline Co. The change in material anisotropy from in-plane to weak perpendicular magnetic anisotropy (wPMA) modifies the basic domain structure and relevant topological defects in the magnetization in each case: from in-plane domains, vortices, antivortices and half vortices in Co lattices to parallel stripe patterns with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Contrast profiles of the asymmetric potentials have been extracted from experimental and simulated MFM data. The experimental distribution of asymmetric Néel walls was obtained by using 24 a NANOTECH Atomic Force Microscope system with magnetic NANOSENSORS. The micromagnetic simulations were carried out with the finite difference code MuMax3 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast profiles of the asymmetric potentials have been extracted from experimental and simulated MFM data. The experimental distribution of asymmetric Néel walls was obtained by using 24 a NANOTECH Atomic Force Microscope system with magnetic NANOSENSORS. The micromagnetic simulations were carried out with the finite difference code MuMax3 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The experimental distribution of magnetic charges was obtained by using a Nanotech™ Atomic Force Microscope system with magnetic Nanosensors™ (20). Magnetic Force Microscopy (MFM) contrast was used as a proxy for the potential asymmetric landscape of the nanomagnets.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In a recent publication, Valdes-Bango et al have reported a rich multidomain magnetic scenario in Co and NdCo honeycomb lattices [40] with large dimensions (2 μm bar length/ 1 μm bar width). In this case, we have chosen a Co honeycomb structure (see figure 1(a)) with small dimensions to favor single domain states in each Co bar, which is a necessary condition for the observation of artificial spin ice behavior.…”
Section: Magnetic Characterizationmentioning
confidence: 99%